“It’s Time for a Rent Strike”: COVID-19 Rent Strikes and the Absence of State Care - Valentine Riley (Open Philosophy, 2022)
COVID-19 unemployed millions of Americans, many of whom already lacked the financial ability to withstand an economic crisis. Mid-quarantine, politicians began to grapple on what protections for renters would stay in place as the assistance bills came to an end. The COVID-19 rent crisis raised significant moral questions to the American populace – namely, that of the State’s responsibility to care for its citizens. This article examines rent strikes in the context of care ethics. Care ethics contends that our actions have moral weight. What we do matters. Rent strikes sit at the intersection of political practice and care ethics. This article contends that rent strikes provided care when the State did not, and that this lack of care highlights the need for solidarity.